Trends in preterm birth in the Netherlands in 2011–2019: A population‐based study among singletons and multiples - Job Klumper; Anita C. J. Ravelli; Carolien Roos; Ameen Abu‐Hanna; Martijn A. Oudijk (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Preterm birth (PTB) is the leading cause of infant mortality and morbidity worldwide. Rates of PTB in the Netherlands are declining, possibly due to the implementation of preventive strategies. In this study we assessed the overall trend in PTB rates in the Netherlands in recent years, and in more detail in specific subgroups to investigate potential groups that require scrutiny in the near future. Material and methods Based on the national perinatal registry, we included all pregnancies without severe congenital abnormalities resulting in a birth from 24 to 42 completed weeks of gestation between 2011 and 2019 in the Netherlands. We assessed PTB rates in two different clinical subtypes (spontaneous vs. iatrogenic) and in five gestational age subgroups: 24–27+6 weeks (extreme), 28–31+6 weeks (very), 32–33+6 weeks (moderate, 34–36+6 weeks [late] and, in general, 24–36+6 weeks [overall PTB]). Trend analysis was performed using the Cochran Armitage test. We also compared PTB rates in different subgroups in the first 2 years compared to the last 2 years. Singleton and multiple gestations were analyzed separately. Results We included 1 447 689 singleton and 23 250 multiple pregnancies in our study. In singletons, we observed a significant decline in PTB from 5.5% to 5.0% (p < 0.0001), mainly due to a decrease in iatrogenic PTBs. When focusing on different gestational age subgroups, there was a decrease in all iatrogenic PTB and in moderate to late spontaneous PTB. However, in spontaneous extreme and very PTB there was an significant increase. When assessing overall PTB risk in different subgroups, the decline was only visible in women with age ≥25 years, nulliparous and primiparous women, women with a medium or high socioeconomic status and hypertensive women. In multiples, the rate of PTB remained fairly stable, from 52.3% in 2011 to 54.1% in 2019 (p = 0.57). Conclusions In the Netherlands, between 2011 and 2019, PTB decreased, mainly due to a reduction in late PTB, and more in iatrogenic than in spontaneous PTB. Focus for the near future should be on specific subgroups in which the decline was not visible, such as women with a low socioeconomic status or a young age.